Exploring Biocontrol Agents From Microbial Keystone Taxa Associated to Suppressive Soil: A New Attempt for a Biocontrol Strategy - Zheng, Yanfen; Han, Xiaobin; Zhao, Donglin; Wei, Keke; Yuan, Yuan; Li, Yiqiang; Liu, Minghong; Zhang, Cheng-Sheng (Frontiers in Plant Science, 2021)
Recent studies have observed differing microbiomes between disease suppressive and conducive soils. However, it remains unclear whether the microbial keystone taxa in suppressive soil are critical for the suppression of diseases. Bacterial wilt is a common soil-borne disease caused by Ralstonia solanacearum that affects tobacco plants. In this study, two contrasting tobacco fields with bacterial wilt disease incidences of 0% (disease suppressive) and 100% (disease conducive) were observed. Through amplicon sequencing, as expected, a high abundance of Ralstonia was found in the disease conducive soil, while large amounts of potential beneficial bacteria were found in the disease suppressive soil. In the fungal community, an abundance of the Fusarium genus, which contains species that cause Fusarium wilt, showed a positive correlation (P < 0.001) with the abundance of Ralstonia. Network analysis revealed that the healthy plants had more complex bacterial networks than the diseased plants. A total of 9 and 13 bacterial keystone taxa were identified from the disease-suppressive soils and healthy roots, respectively. Accumulated abundance of these bacterial keystones showed a negative correlation (P < 0.001) with the abundance of Ralstonia. To complement network analysis, culturable strains were isolated, and three species belonging to Pseudomonas showed high 16S rRNA gene similarity (98.4-100%) with keystone taxa. These strains displayed strong inhibition on pathogens and reduced the incidence of bacterial wilt disease in greenhouse condition. This study highlighted the importance of keystone species in the protection of crops against pathogen infection and proposed an approach to obtain beneficial bacteria through identifying keystone species, avoiding large-scale bacterial isolation and cultivation.